Malay interrogative knowledge corpus - Sidi, Fatimah; A. Jabar, Marzanah; Selamat, Mohd Hasan; Abd Ghani, Abdul Azim; Sulaiman, Md. Nasir; Baharom, Salmi (Science Publications, 2011)
Problem statement: The growth in the number of documents written in Malay language is enormously available on the web and intranets. There is a need to identify the information in the Malay documents that contain knowledge. This triggers the need to investigate the availability of knowledge in them. Approach: This study uses interrogative theory to identify knowledge from documents or texts. Results: The results are expected to lead towards establishment of new set of interrogative rules for Malay corpus. Conclusions/Recommendations: This study contributes the interrogative knowledge identification thru the development of Malay Interrogative Knowledge Corpus (MalayIKCorpus). It facilitates to explicitly capture and make available Malay knowledge representation in a knowledge-base system.